The Purple revolution. Spain 2014-2015 = Purpurowa rewolucja. Hiszpania 2014-2015 - Tarnawski, Eduard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author attempts to guess whether Spain is on the eve of a new revolution. He excludes that it is possible to research it on the basis of analyzes derived from economic determinism or historiosophic fatalism. He does not expect the plots to be helpful, which fiction literature or reportage can provide. In return, he proposes to use the possibilities of interpretation offered by Edmund Burke in "Reflections on the Revolution in France".
Keywords: Podemos; Burke, Edmund (1729-1797); escrache; coronation; koronacja